Determination of Initial Unconditional Solution of Heat Conductivity Equation for Evaluation of Temperature Variance in Finite Soil Layer - Ekberlı, I. (My University, 2006)
Soil temperature has very significant effect on biological development of plant and physical, chemical, biological properties of soil. The variance of temperature depending on time and soil depth forms heat transportation and therefore it enables constitution of temperature regime. In this research, it has been determined with a help of experiments (held on 01-17 June, 2005) that daily average temperature on soil surface varies between 24.3-41.9°C and temperature amplitude varies between 7.1-12.5°C. In 10, 20, 30, 40, 50 and 60 cm of soil depth, average temperature, amplitude and diffusivity vary between intervals of 19.5-23.8°C; 0.6-3.5°C; 0.13 × 10-3 -2.51 × 10-3 (cm2 sec-1), consecutively. The initial unconditional solution of heat conductivity equation in T (0, τ) = Tor + T0cosωτ in finite soil layer depending on condition of T (l, τ) ≈ 0 has been determined. The obtained solution, average temperature of soil layer, amplitude and diffusivity enable determination of temperature variance along soil layer depending on time. Based on the obtained solution, it has been determined that relative error between the calculated and observed temperature varies in interval of %2.41-5.66. © 2006 Asian Network for Scientific Information.
Keywords: Harmonic Variance; Heat Conductivity Equation; Limit Conditions; Model; Temperature